Sustainability Assessment of Fruit and Nut Crops in North Florida and North Central Florida - Peter C. Andersen; Jeffrey G. Williamson; Timothy E. Crocker (EDIS)
Revised! HS-765, an 18-page illustrated article by Peter C. Andersen, Jeffrey G. Williamson, and Timothy E. Crocker, summarizes the degree of adaptation of deciduous fruit and nut species in Florida and identifies cultivars that are recommended for trial in various locations in Florida. Includes references. Published by the UF Department of Horticultural Sciences, September 2009.